Hydrated crystalline form of 2-acrylamido-2-methylpropanesulfonic acid

The production of a hydrated crystal form of 2-acrylamide-2-methylopanthrophonic acid addresses the handling and processing challenges of needle-like crystals by enhancing safety and processing properties, resulting in a form suitable for polymer production.

JP7624954B2Active Publication Date: 2025-01-31SPSM SA
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2022166904
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2017-03-20
Filing Date
2022-10-18
Publication Date
2025-01-31
Estimated Expiration
2038-03-19

AI Technical Summary

Technical Problem

The existing methods for producing 2-acrylamide-2-methylopanthrophonic acid result in needle-like crystals that are difficult to handle, transport, and process due to poor solid liquidity, low cohesion, and high explosivity, along with issues related to low crystal grain size and fine dust density.

Method used

The production of a hydrated crystal form of 2-acrylamide-2-methylopanthrophonic acid through a controlled process involving mixing with an aqueous solution, heating, cooling, and separating the solid-liquid phases to achieve a hydrate crystal form with improved handling and processing characteristics.

Benefits of technology

The hydrated crystal form exhibits enhanced safety and processing properties, reducing the risk of explosions and improving handling, with a larger particle size and lower explosivity, making it suitable for applications in polymer production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007624954000005
    Figure 0007624954000005
  • Figure 0007624954000006
    Figure 0007624954000006
  • Figure 0007624954000007
    Figure 0007624954000007
Patent Text Reader

Abstract

To provide (co)polymers having improved properties in terms of filterability and improved chemical and thermal stability compared to polymers made from conventional ATBS. [Solution] The above problem is solved by a (co)polymer obtained from at least the acid form and / or the salified form of 2-acrylamido-2-methylpropanesulfonic acid, wherein at least a portion of the 2-acrylamido-2-methylpropanesulfonic acid is in a hydrated crystalline form and has a powder X-ray diffraction pattern including peaks at 10.58°, 11.2°, 12.65°, 13.66°, 16.28°, 18.45°, 20°, 20.4°, 22.5°, 25.5°, 25.88°, 26.47°, 28.52°, 30.28°, 30.8°, 34.09°, 38.19°, 40.69°, 41.82°, 43.74°, and 46.04° degrees 2-theta (+ / - 0.1°).
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The field of the invention relates to crystalline forms of 2-acrylamido-2-methylpropanesulfonic acid (ATBS). More specifically, the invention relates to hydrated crystalline forms of 2-acrylamido-2-methylpropanesulfonic acid. The invention also relates to a method for producing the hydrated crystalline forms of 2-acrylamido-2-methylpropanesulfonic acid. [Background technology]

[0002] 2-Acrylamido-2-methylpropanesulfonic acid, also known as ATBS, is widely used as an additive in acrylic fibers and as a raw material to produce polymers used as dispersants, flocculant thickeners, or superabsorbents in various fields such as the petroleum industry, construction, textiles, water treatment (seawater desalination, mineral industry, etc.), and cosmetics.

[0003] The reaction used in the preparation of 2-acrylamido-2-methylpropanesulfonic acid is as follows: in which acrylonitrile is present in excess so as to be both the reaction solvent and reagent: Acrylonitrile is contacted with oleum and isobutylene.

[0004] [ka]

[0005] A by-product that may be produced during this synthesis is acrylamide.

[0006] 2-Acrylamido-2-methylpropanesulfonic acid is not soluble in the solvent acrylonitrile, therefore the reaction product is in the form of a crystalline suspension in the reaction solvent.

[0007] For example, documents U.S. Patent No. 6,448,347 and Chinese Patent No. 102351744 describe a method for continuously producing 2-acrylamido-2-methylpropanesulfonic acid, which is then separated from acrylonitrile, typically by filtration, and then dried.

[0008] Drying the 2-acrylamido-2-methylpropanesulfonic acid is necessary to reduce the residual amounts of acrylonitrile and acrylamide present in the crystals. These two compounds are classified as carcinogenic, mutagenic, or toxic to reproduction (CMR). It is therefore necessary to proceed with effective filtration to remove as much acrylonitrile as possible, and then to dry the 2-acrylamido-2-methylpropanesulfonic acid to obtain a low content of acrylonitrile and acrylamide.

[0009] Those skilled in the art know that crystals of 2-acrylamido-2-methylpropanesulfonic acid have a crystalline arrangement that produces needle-like solids.

[0010] Those skilled in the art know that needle-shaped crystals exhibit macroscopic properties that make solid handling and transportation difficult (poor solid flowability, clumping, low resistance to shear forces) and processing difficult (poor filterability, difficult drying, attrition).

[0011] In the case of 2-acrylamido-2-methylpropanesulfonic acid, additional problems encountered are the typically low crystal size in the case of needle-like crystals, the density of the solids, and the explosibility of the fine dust.

[0012] These macroscopic properties are directly related to the crystal morphology and the specific surface area of ​​the crystals, which is high for needle-shaped crystals.

[0013] WO 2009 / 072480, JP 2008 / 307822, and JP 2003 / 137857 disclose that the crystals of 2-acrylamido-2-methylpropanesulfonic acid obtained are needle-shaped. [Prior art documents] [Patent documents]

[0014] [Patent Document 1] U.S. Patent No. 6,448,347 [Patent Document 2] Chinese Patent No. 102351744 [Patent Document 3] International Publication No. 2009 / 072480 [Patent Document 4] Patent Publication 2008 / 307822 [Patent Document 5] Patent Publication 2003 / 137857 Summary of the Invention [Means for solving the problem]

[0015] The present invention relates to a particular form of 2-acrylamido-2-methylpropanesulfonic acid, hereinafter referred to as "hydrated crystalline form of 2-acrylamido-2-methylpropanesulfonic acid."

[0016] Another feature of the present invention is a method for producing a hydrated crystalline form of 2-acrylamido-2-methylpropanesulfonic acid.

[0017] The present invention also relates to aqueous solutions of 2-acrylamido-2-methylpropanesulfonic acid salts prepared from the hydrated crystalline form of 2-acrylamido-2-methylpropanesulfonic acid.

[0018] The present invention also relates to the use of the hydrated crystalline form of 2-acrylamido-2-methylpropanesulfonic acid for the preparation of water-soluble, water-swellable or superabsorbent (co)polymers.

[0019] Another aspect of the present invention relates to the use of (co)polymers made from the hydrated crystalline form of 2-acrylamido-2-methylpropanesulfonic acid, more particularly in the field of enhanced oil and gas recovery. [Brief description of the drawings]

[0020] [Figure 1] FIG. 2 is a diagram showing the proton NMR spectrum of the 2-acrylamido-2-methylpropanesulfonic acid crystals obtained according to Examples 1 and 2. [Diagram 2] FIG. 1 is an X-ray diffraction pattern of the crystals obtained according to Example 1. [Diagram 3] FIG. 1 is an X-ray diffraction diagram of the crystals obtained according to Example 2. [Figure 4] FIG. 1 is a diagram showing the Fourier transform infrared spectrum of the crystals obtained in Example 1. [Diagram 5] FIG. 1 is an X-ray diffraction diagram of the crystals obtained according to Example 2. [Figure 6] FIG. 2 shows a thermogram of the crystals obtained according to Example 1. [Figure 7] FIG. 2 shows a thermogram of the crystals obtained according to Example 2. [Figure 8] FIG. 2 is a graph showing the particle size of the crystals obtained according to Example 1. [Figure 9] FIG. 1 shows a graph of the particle size of the crystals obtained according to Example 2. [Figure 10] FIG. 2 is a diagram corresponding to the result of optical microscope observation of the crystals obtained according to Example 1. [Figure 11] FIG. 11 is a diagram corresponding to the result of optical microscope observation of the crystals obtained according to Example 2. [Figure 12] FIG. 2 is a diagram corresponding to the result of scanning electron microscope observation of the crystals obtained according to Example 1. [Figure 13] FIG. 2 is a diagram corresponding to the results of scanning electron microscope observation of the crystals obtained according to Example 2. [Figure 14] FIG. 1 shows viscosity reduction as a function of ATBS morphology and iron content for copolymers. [Figure 15] FIG. 1 shows the viscosity decrease upon 90° C. aging for copolymers as a function of ATBS morphology. [Figure 16] FIG. 1 shows viscosity reduction as a function of ATBS morphology and iron content for homopolymers. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] The present invention relates to a hydrated crystalline form of 2-acrylamido-2-methylpropanesulfonic acid having a 2-theta powder X-ray diffraction pattern including peaks at 10.58°, 11.2°, 12.65°, 13.66°, 16.28°, 18.45°, 20°, 20.4°, 22.5°, 25.5°, 25.88°, 26.47°, 28.52°, 30.28°, 30.8°, 34.09°, 38.19°, 40.69°, 41.82°, 43.74°, 46.04° degrees. The uncertainty of these peaks is generally on the order of 0.1°.

[0022] X-ray crystallography, radiometric crystallography, or X-ray diffractometry, is an analytical technique for studying the structure of crystalline materials at the atomic scale. It uses the physical phenomenon of X-ray diffraction. A diffractometer with a copper source may be used.

[0023] A powder formed from a certain crystalline phase always gives rise to diffraction peaks in the same direction, so the diffraction pattern forms the actual signature of the crystalline phase, and it is therefore possible to identify the nature of each crystalline phase in a mixture or in a pure product.

[0024] This signature is specific for each organic or inorganic compound and is expressed in the form of a list of peaks with their positions in 2θ angles (2 theta).

[0025] This technique is used to identify materials, and in particular to identify the different crystalline forms that may exist for a given chemical molecule.

[0026] The present invention also relates to a method for producing a 3280 cm -1 , 3126cm-1 , 1657cm -1 , 1595cm -1 , 1453cm -1 , 1395cm -1 , 1307cm -1 , 1205cm -1 , 1164cm -1 , 1113cm -1 , 1041cm -1 , 968cm -1 , 885cm -1 , 815cm -1 , 794cm -1 The present invention also relates to a hydrated crystalline form of 2-acrylamido-2-methylpropanesulfonic acid having a Fourier transform infrared spectrum containing peaks at 8 cm. The uncertainty of these peaks is generally within 8 cm. -1 Advantageously, this is a solid state spectrum traditionally obtained with a salt such as KBr.

[0027] Fourier transform infrared spectroscopy is the analysis of vibrations emitted, absorbed or diffused by molecules. This technique is sensitive to close-range interactions (effects on the bonds of lattice units). In most cases, the Fourier transform infrared spectra of different crystal systems are significantly different. Thus, the Fourier transform infrared spectrum reflects details about the crystal structure of organic compounds.

[0028] Typically, and unless otherwise stated, X-ray diffractograms and infrared spectra are obtained at 20° C. and 1 atmosphere atmospheric pressure (101325 Pa).

[0029] The present invention also relates to hydrated crystalline forms of 2-acrylamido-2-methylpropanesulfonic acid having a minimum ignition energy of greater than 400 mJ, preferably greater than 500 mJ.

[0030] The minimum ignition energy represents the minimum energy that must be provided to ignite a compound. The energy can be electrical or thermal energy. The minimum ignition energy is essential data to consider the risk of explosion during the handling of a product (transport, storage, reaction, molding, etc.).

[0031] The minimum ignition energy depends on the powder's properties (composition) and its macromolecular structure (particle size, crystal shape, specific surface area).

[0032] For solids, this energy is the minimum energy of an electric spark capable of igniting a dust cloud. The higher the minimum ignition energy, the lower the risk that the solid poses during use, handling and storage.

[0033] The minimum ignition energy was determined according to standard NF EN 13821.

[0034] The present invention also relates to a hydrated crystalline form of 2-acrylamido-2-methylpropanesulfonic acid which exhibits four thermal phenomena using differential scanning calorimetry at 70° C., 100° C., 150° C., and 190° C. The relative uncertainty in the observation of these phenomena is generally of the order of 10° C., advantageously of the order of less than 5° C.

[0035] Thermal phenomena are measured by differential scanning calorimetry (DSC), a technique that measures the heat fluctuations associated with the thermal denaturation of a compound when it is heated at a constant rate, e.g., a heating ramp of 10° C. / min.

[0036] It is generally recognized that the thermal phenomenon occurring at 190°C (+ / - 10°C) is related to the melting point of 2-acrylamido-2-methylpropanesulfonic acid.

[0037] In an advantageous manner, the water / 2-acrylamido-2-methylpropanesulfonic acid molar ratio of the hydrated crystalline form of 2-acrylamido-2-methylpropanesulfonic acid according to the invention is 1.

[0038] The present invention also provides a method for producing a hydrated crystalline form of 2-acrylamido-2-methylpropanesulfonic acid, comprising at least the following successive steps: 1) mixing 2-acrylamido-2-methylpropanesulfonic acid with an aqueous solution, advantageously for at least 1 minute, to form suspension A; 2) heating suspension A, advantageously to a temperature between 40 and 150° C., to prepare a solution B of 2-acrylamido-2-methylpropanesulfonic acid, 3) cooling solution B to a temperature advantageously between −40 and 100° C., advantageously over a period of 1 to 1200 minutes, to obtain a suspension C of crystals, 4) carrying out a solid / liquid separation from suspension C and isolating crystals in the form of composition 1 from suspension C obtained from step 3), the crystals advantageously representing between 40 and 99% by weight of composition 1. The crystals obtained are in a hydrated crystalline form.

[0039] The temperature of steps 2) and 3) may vary, particularly depending on the concentration of 2-acrylamido-2-methylpropanesulfonic acid. A person skilled in the art will know how to adapt the temperature variations to optimize crystal formation.

[0040] Process 1): 2-Acrylamido-2-methylpropanesulfonic acid is obtained from the manufacturing methods already mentioned (acrylonitrile, oleum, and isobutylene). 2-Acrylamido-2-methylpropanesulfonic acid may be in the form of a fine powder or may be shaped in a controlled manner by methods such as compression, granulation, or extrusion.

[0041] The mass ratio of the aqueous solution mixed with 2-acrylamido-2-methylpropanesulfonic acid is advantageously between 0.1:1 and 5:1, more preferably between 0.2:1 and 3:1.

[0042] According to a particular embodiment, the aqueous solution may comprise up to 20% by weight of organic solvent 1, preferably 1-15% by weight of organic solvent 1, more preferably 2-10% by weight of organic solvent 1.

[0043] According to another particular embodiment of the invention, the aqueous solution comprises at least 80% by weight of water and up to 20% by weight of organic solvent 1, preferably 85% to 99% by weight of water and 1% to 15% by weight of organic solvent 1, more preferably 90% to 98% by weight of water and 2% to 10% by weight of organic solvent 1.

[0044] The organic solvent 1 is advantageously chosen from the following compounds: - organic acids, preferably carboxylic acids containing from 1 to 8 carbons; amides, advantageously containing from 1 to 8 carbon atoms, alcohols advantageously containing from 1 to 8 carbon atoms, ketones, advantageously containing from 1 to 8 carbon atoms, ethers advantageously containing from 1 to 8 carbon atoms, esters advantageously containing from 1 to 8 carbon atoms, alkanes, advantageously containing from 1 to 8 carbon atoms, halogenated hydrocarbon compounds, advantageously containing from 1 to 8 carbon atoms, nitriles, advantageously containing from 1 to 8 carbon atoms, or - A mixture of these.

[0045] These compounds may be linear or branched. They may be saturated or contain unsaturation, for example C≡N in the case of nitriles.

[0046] Preferably, solvent 1 is selected from acrylonitrile, isopropanol, acetic acid, or a mixture thereof. Preferably, solvent 1 is acrylonitrile.

[0047] Solvent 1 is generally in liquid form at the temperature at which steps 2) and 3) are carried out. In addition, it is advantageously miscible with water.

[0048] Solvent 1 may, if necessary, solubilize any impurities or by-products present with the 2-acrylamido-2-methylpropanesulfonic acid used to form Suspension A. In contrast, 2-acrylamido-2-methylpropanesulfonic acid does not need to be soluble in Solvent 1.

[0049] According to another particular embodiment of the invention, the aqueous solution may comprise at least 80% by weight of water and up to 20% by weight of inorganic acid, preferably 80% to 99% by weight of water and 1% to 20% by weight of inorganic acid, more preferably 85% to 98% by weight of water and 2% to 15% by weight of inorganic acid.

[0050] Preferably, the inorganic acid is sulfuric acid. In this case, an aqueous solution of sulfuric acid can be prepared by diluting an acid containing less than 80% water or an acid containing less than 80% of a source of SO3, such as oleum or sulfur trioxide.

[0051] Thus, the aqueous solution may comprise at least one organic solvent 1 and / or at least one inorganic acid other than 2-acrylamido-2-methylpropanesulfonic acid.

[0052] The mixing time of the aqueous solution and the 2-acrylamido-2-methylpropanesulfonic acid is advantageously at least 1 minute. During mixing, the aqueous solution may be added sequentially before or after the 2-acrylamido-2-methylpropanesulfonic acid. During mixing, the aqueous solution and the 2-acrylamido-2-methylpropanesulfonic acid may be added simultaneously.

[0053] The mixing temperature is generally below 40° C. The lower temperature limit is limited by the melting temperature of the aqueous solution or suspension A.

[0054] The products of step 1) can be mixed using various techniques. As non-limiting examples, we can mention stirred reactors, loop reactors, static mixers, microreactors, plug flow reactors, stirred filter dryer reactors such as Nutsche, paddle blenders, double cone blenders, plow blenders, and disc blenders.

[0055] Process 2): The suspension A obtained in step 1) is heated to a temperature of 40 to 150° C., more preferably to a temperature of 50 to 120° C., to prepare a solution B.

[0056] The time for Solution B to reach that temperature does not affect the benefits of the present invention.

[0057] Various techniques may be used to achieve the temperature increase of suspension A to prepare solution B. As non-limiting examples, we can mention stirred reactors, loop reactors, static mixers, microreactors, plug flow reactors, stirred filter-drier reactors such as Nutsche, heat exchangers, paddle blenders, double cone blenders, plow blenders, disc blenders, falling film evaporators, thin film evaporators, and reboilers.

[0058] Step 2) solubilizes 2-acrylamido-2-methylpropanesulfonic acid.

[0059] In a particular embodiment of the invention, solution B may be subjected to a solid / liquid separation operation in order to remove any insoluble particles.

[0060] Step 3: Solution B obtained in step 2) is cooled to a temperature of −40 to 100° C., more preferably to a temperature of −20 to 50° C. As already indicated, the skilled person will know how to adjust the temperature depending on the concentration of 2-acrylamido-2-methylpropanesulfonic acid and / or depending on the melting point of solvent 1 and / or depending on the inorganic acid of step 1).

[0061] Generally, the temperature in step 3) is lower than the temperature in step 2).

[0062] The cooling time is advantageously between 1 minute and 1200 minutes.

[0063] The cooling rate does not have to be constant throughout the process. For example, solution B may be cooled at 5° C. per hour for the first 3 hours, and then at a rate of 10° C. per hour until the final temperature is reached.

[0064] During cooling of solution B, crystals of 2-acrylamido-2-methylpropanesulfonic acid form and precipitate, forming suspension C.

[0065] Various techniques may be used to achieve the cooling of solution B to prepare suspension C. As non-limiting examples, we can mention stirred reactors, loop reactors, static mixers, microreactors, plug flow reactors, stirred filter-drier reactors such as Nutsche, heat exchangers, paddle blenders, double cone blenders, plow blenders, disc blenders, falling film evaporators, thin film evaporators, and unstirred reactors.

[0066] In a particular embodiment of the invention, pre-prepared hydrated crystals of 2-acrylamido-2-methylpropanesulfonic acid may be added during this step to improve the formation of suspension C. This is seeding and may lead to better control of crystallization temperature, crystal size, size distribution, final product purity, and, if desired, yield.

[0067] Step 4: The crystals of hydrated 2-acrylamido-2-methylpropanesulfonic acid contained in suspension C obtained in step 3) are isolated through a liquid / solid separation step, and obtained in the form of composition 1. As non-limiting examples, the inventors can mention a centrifugal filter, a decanter, a filter press, a smoothing filter with a stirrer, a belt filter, a disk filter, or a rotary drum filter. In a preferred method, the liquid / solid separation is carried out using a centrifugal filter. The liquid / solid separation may also be carried out by gravity decantation.

[0068] Step 4) is advantageously carried out at a temperature of from -40 to 100°C, more preferably from -20 to 50°C.

[0069] Preferably, after liquid / solid separation step 4), the crystals of 2-acrylamido-2-methylpropanesulfonic acid are not dried.

[0070] The isolated composition 1 advantageously has a crystalline content of 2-acrylamido-2-methylpropanesulfonic acid of 40-99% by weight, more preferably 60-99% by weight, even more preferably 60-98% by weight. The remainder of the composition 1 mainly comprises water.

[0071] After step 4), the crystals of 2-acrylamido-2-methylpropanesulfonic acid are characterized as being crystals of 2-acrylamido-2-methylpropanesulfonic acid in a hydrated form.

[0072] Furthermore, the liquid phase obtained after liquid / solid separation contains mainly water and saturated 2-acrylamido-2-methylpropanesulfonic acid, as well as small amounts of organic solvent 1 and / or inorganic acid. According to a particular embodiment of the invention, this liquid phase after separation may be used in whole or in part for the aqueous solution of step 1).

[0073] Step 5): In an optional step 5), the crystal-containing composition 1 obtained from step 4) is washed with a washing solution.

[0074] The washing solution is advantageously an aqueous solution which may contain up to 20% of an organic solvent 1.

[0075] Preferably, the cleaning solution comprises at least 80% by mass of water and up to 20% by mass of organic solvent 1, preferably 80% to 99% by mass of water and 1% to 20% by mass of organic solvent 1, and more preferably 85% to 98% by mass of water and 2% to 15% by mass of organic solvent 1.

[0076] As already mentioned, the organic solvent 1 is selected from organic acids, amides, alcohols, ketones, ethers, esters, alkanes, halogenated hydrocarbon compounds, nitriles, or mixtures thereof. Preferably, the solvent 1 is selected from acrylonitrile, isopropanol, acetic acid, or mixtures thereof. More preferably, the solvent 1 is acrylonitrile.

[0077] According to a particular embodiment of the invention, the washing of the composition 1 obtained from step 4) is carried out by spraying said composition 1 with a washing solution.

[0078] According to another particular embodiment of the invention, the washing of composition 1 obtained from step 4) is carried out by suspending said composition 1 in a washing solution.

[0079] The weight ratio between the aqueous cleaning solution and the composition 1 obtained from step 4) is advantageously between 0.05:1 and 10:1, more preferably between 0.1:1 and 5:1.

[0080] This washing step is advantageously carried out at a temperature between −20 and 100° C. The person skilled in the art will know how to adjust the temperature so that the crystals of 2-acrylamido-2-methylpropanesulfonic acid in hydrated form are not solubilized.

[0081] According to certain embodiments, the aqueous cleaning solution may contain up to 60% by weight of 2-acrylamido-2-methylpropanesulfonic acid.

[0082] The hydrated form of crystalline 2-acrylamido-2-methylpropanesulfonic acid obtained from optional step 5) may be isolated in the form of composition 2 from the washing solution by a liquid / solid separation step. As non-limiting examples, we may mention the use of vertical or horizontal centrifugal filters, decanters, filter presses, belt filters, disc filters, pressure filters or rotary drum filters. The liquid / solid separation may be carried out by gravity decantation.

[0083] According to a particular embodiment of the invention, the recovered washing solution may be totally or partially reused in step 5) with or without a previous treatment step.

[0084] According to a particular embodiment of the invention, the cleaning solution may be used, in whole or in part, in the aqueous solution of step 1), with or without a prior treatment step.

[0085] Step 6): In an optional step 6), the composition 2 obtained in step 5) is dried. By way of non-limiting example, the inventors can mention the use of all convection, conduction or radiation drying techniques (fluidized bed dryer, traversed bed dryer, conveyor belt drying, microwave drying on a heated, stirrer-equipped smoothing filter, drying by radio frequency radiation, infrared, spray drying).

[0086] The drying operation may be carried out at atmospheric pressure or under vacuum.

[0087] The drying process may be carried out in batches or continuously.

[0088] During the preparation process, i.e. during steps 1) to 6), and regardless of the step, at least one polymerization inhibitor can be added to prevent any polymerization of 2-acrylamido-2-methylpropanesulfonic acid. This inhibitor may be selected from, but is not limited to, hydroquinone, paramethoxyphenol, phenothiazine, 2,2,6,6-tetramethyl(piperidin-1-yl)oxyl, 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxyl, phenylenediamine derivatives, or mixtures thereof.

[0089] Preferably, the inhibitor is paramethoxyphenol or 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxyl.

[0090] The amount of inhibitor added relative to the amount of 2-acrylamido-2-methylpropanesulfonic acid added in step 1) is advantageously between 0.001% and 5% by weight, more preferably between 0.01% and 1% by weight.

[0091] The inhibitor may be added during one or more steps of the process. Preferentially, it is added as an additional amount during step 1). More preferably, the inhibitor forms part of the aqueous solution added in step 1).

[0092] The production process (steps 1) to 6)) may be carried out continuously or discontinuously (batchwise).

[0093] The present invention also relates to a method for preparing an aqueous solution A of 2-acrylamido-2-methylpropanesulfonate prepared from the hydrated crystalline form.

[0094] The method for preparing the aqueous solution A of 2-acrylamido-2-methylpropanesulfonate comprises the following steps: a) preparing an aqueous solution X of 2-acrylamido-2-methylpropanesulfonic acid, advantageously having a concentration between 1 and 700 g / L, b) contacting and mixing the aqueous solution X with a compound Y chosen from alkali metal or alkaline earth metal hydroxides, alkali metal or alkaline earth metal oxides, ammonia, amines having the following formula NR1R2R3, where R1, R2 and R3 are advantageously hydrocarbon radicals, in particular alkyl radicals, or alkali metal or alkaline earth metal carbonates; Includes.

[0095] Step a): The hydrated crystalline form of 2-acrylamido-2-methylpropanesulfonic acid may be in the form of a fine powder or may be shaped in a controlled manner by methods such as compression, or granulation, or extrusion.

[0096] The aqueous solution X of 2-acrylamido-2-methylpropanesulfonic acid is advantageously prepared by mixing a hydrated crystalline form of 2-acrylamido-2-methylpropanesulfonic acid with an aqueous solution Z.

[0097] The mixing time of the aqueous solution Z and the 2-acrylamido-2-methylpropanesulfonic acid is advantageously at least 1 minute. During mixing, the aqueous solution Z and the 2-acrylamido-2-methylpropanesulfonic acid may be added simultaneously without a preferred order or may be added simultaneously.

[0098] The mixing temperature is generally lower than 60° C. The lower limit of the temperature is limited by the crystallization temperature of the aqueous solution Z or the crystallization temperature of the aqueous solution X of 2-acrylamido-2-methylpropanesulfonic acid.

[0099] Aqueous solution Z is composed primarily of water and may contain 2-acrylamido-2-methylpropanesulfonic acid or a salt thereof previously prepared from any of the bases listed above (compound Y).

[0100] The products of step a) can be mixed using various techniques: by way of non-limiting examples we can mention stirred reactors, loop reactors, static mixers, microreactors, plug flow reactors, stirred filter-drier reactors such as Nutsche, paddle blenders, double cone blenders, plow blenders, and disc blenders.

[0101] Step b): Compound Y may be in solid or liquid form.

[0102] According to a particular embodiment of the invention, compound Y is in the form of a solid, preferably in the form of a powder or shaped in a controlled manner, such as by methods such as compression, or granulation, or extrusion.

[0103] According to another particular embodiment, the compound Y is in the form of a liquid, preferably in the form of an aqueous solution Y.

[0104] When compound Y is an alkali metal or alkaline earth metal hydroxide, it may be chosen from sodium hydroxide, potassium hydroxide, lithium hydroxide, magnesium hydroxide and calcium hydroxide.

[0105] When compound Y is an alkaline earth metal oxide, it may be chosen from calcium oxide and magnesium oxide.

[0106] When compound Y is an amine having the formula NR1R2R3, where R1, R2 and R3 are independently hydrogen atoms or carbon chains having 1 to 22 carbon atoms, preferably linear, R1, R2 and R3 are not simultaneously hydrogen atoms. In general, ammonia (NH3) is preferred over amines having the formula NR1R2R3.

[0107] In a preferred process, compound Y is an aqueous solution of an alkali metal or alkaline earth metal hydroxide. Preferably, the alkali metal hydroxide is sodium hydroxide.

[0108] When compound Y is in the form of an aqueous solution Y, the concentration of compound Y in the solution is advantageously from 0.1 to 70% by mass.

[0109] During mixing of aqueous solution X with aqueous solution Y, the temperature is advantageously maintained between -10 and 60°C, preferably between 0 and 30°C.

[0110] The molar ratio between 2-acrylamido-2-methylpropanesulfonic acid and compound Y is advantageously between 1:0.1 and 1:1.1, more preferably between 1:0.5 and 1:1.05.

[0111] During mixing, the aqueous solution X may be added sequentially before or after the compound Y (or the aqueous solution Y). During mixing, the aqueous solution X and the compound Y (or the aqueous solution thereof) may be added simultaneously.

[0112] Preferably, the aqueous solution X is added first, followed by the compound Y (or its aqueous solution Y).

[0113] Regardless of the process, during the preparation of solution A of 2-acrylamido-2-methylpropanesulfonate prepared from the hydrated crystalline solid form, it is possible to add at least one polymerization inhibitor, which may be selected from, but is not limited to, hydroquinone, paramethoxyphenol, phenothiazine, 2,2,6,6-tetramethyl(piperidin-1-yl)oxyl, 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxyl, phenylenediamine derivatives, or mixtures thereof.

[0114] Preferably, the inhibitor is paramethoxyphenol.

[0115] The present invention also relates to the use of the novel hydrated crystalline forms of 2-acrylamido-2-methylpropanesulfonic acid for the preparation of (co)polymers. This aspect of the present invention also includes the use of salts of the hydrated crystalline forms of 2-acrylamido-2-methylpropanesulfonic acid for the preparation of (co)polymers.

[0116] Very unexpectedly, the applicants have discovered that the (co)polymers according to the invention have improved properties, especially with regard to filterability, as well as improved chemical and thermal stability, compared to polymers made from conventional ATBS, which are particularly useful in enhanced oil or gas recovery techniques from conventional reservoirs, shales or oil sands.

[0117] The present invention therefore relates to a (co)polymer obtained from 2-acrylamido-2-methylpropanesulfonic acid at least in acid form and / or in salified form, at least a portion of which is in hydrated crystalline form and has an X-ray powder diffraction pattern comprising peaks at 10.58°, 11.2°, 12.65°, 13.66°, 16.28°, 18.45°, 20°, 20.4°, 22.5°, 25.5°, 25.88°, 26.47°, 28.52°, 30.28°, 30.8°, 34.09°, 38.19°, 40.69°, 41.82°, 43.74°, 46.04° degrees 2-theta (+ / - 0.1°).

[0118] It may be a copolymer (derived from two or more different monomers) or a homopolymer.

[0119] The monomeric 2-acrylamido-2-methylpropanesulfonic acid in its hydrated crystalline form may be in acid form and / or in salt form, the salts being advantageously obtained from compounds chosen from alkali metal or alkaline earth metal hydroxides, alkali metal or alkaline earth metal oxides, ammonia, amines of the following formula NR1R2R3, or alkali metal or alkaline earth metal carbonates.

[0120] Generally, the salified form of the anionic monomer can be obtained before and / or during and / or after its polymerization. It is advantageously obtained before the polymerization, especially in the case of the hydrated crystalline form of 2-acrylamido-2-methylpropanesulfonic acid.

[0121] According to a particular embodiment of the invention, the polymer is a homopolymer of the hydrated crystalline form of 2-acrylamido-2-methylpropanesulfonic acid.

[0122] According to another particular embodiment of the invention, the (co)polymer is obtained from at least 2-acrylamido-2-methylpropanesulfonic acid, of which 50% to 100%, more preferably 70% to 100%, even more preferably 100% is in hydrated crystalline form.

[0123] The (co)polymer according to the invention is advantageously obtained from 1 to 100 mol % of 2-acrylamido-2-methylpropanesulfonic acid, preferably from 2 to 60 mol % of 2-acrylamido-2-methylpropanesulfonic acid, even more preferably from 3 to 25 mol % of 2-acrylamido-2-methylpropanesulfonic acid, of which 50% to 100%, more preferably 70 to 100%, even more preferably 100% is advantageously in hydrated crystalline form.

[0124] In general, a person skilled in the art will know how to adjust, if necessary, the amount of additional monomers (anionic and / or cationic and / or zwitterionic) that may be optionally present, as listed below, to reach 100 mol %.

[0125] According to another particular embodiment of the invention, the (co)polymer may be obtained from 2-acrylamido-2-methylpropanesulfonic acid, advantageously in hydrated crystalline form, of 50% to 100% (more advantageously 70 to 100%, even more preferred 100%), and at least one nonionic monomer and / or at least one anionic monomer and / or at least one cationic monomer and / or zwitterionic monomer.

[0126] According to another particular embodiment of the invention, the polymer is a copolymer of a hydrated crystalline form of 2-acrylamido-2-methylpropanesulfonic acid and of at least one non-ionic monomer.

[0127] The non-ionic monomer may in particular be selected from the group comprising water-soluble vinyl monomers, in particular acrylamide, N-isopropylacrylamide, N,N-dimethylacrylamide, N-vinylformamide, acryloylmorpholine, N,N-diethylacrylamide, N-tert-butylacrylamide, N-tert-octylacrylamide, N-vinylpyrrolidone, N-vinylcaprolactam, N-vinyl-imidazole, hydroxyethylmethacrylamide, hydroxypropyl acrylate, isoprenol and diacetoneacrylamide. Advantageously, the non-ionic monomer is acrylamide.

[0128] According to a particular embodiment, the copolymer is advantageously obtained from 1 to 99 mol %, preferably from 40 to 95 mol %, more preferably from 45 to 90 mol % of nonionic monomers relative to the total number of monomers, in which case the copolymer is advantageously obtained from 0.1 to 99 mol % of 2-acrylamido-2-methylpropanesulfonic acid, of which 50% to 100%, more preferably from 70 to 100%, even more preferably 100%, is in hydrated crystalline form.

[0129] The anionic monomers may have acrylic, vinyl, maleic, fumaric, malonic, itaconic, or allyl functionality and may contain carboxylate, phosphonate, phosphate, sulfate, sulfonate, or other anionic groups. The anionic monomers may be in the acid form and / or in the form of an alkaline earth metal salt, alkali metal salt, or ammonium salt. Examples of suitable monomers include acrylic acid, methacrylic acid, itaconic acid, crotonic acid, maleic acid, fumaric acid, acrylamido undecanoic acid, acrylamido 3-methylbutanoic acid, maleic anhydride; strong acid type monomers, for example with sulfonic or phosphonic acid type functional groups, such as vinyl sulfonic acid, vinyl phosphonic acid, allyl sulfonic acid, methallyl sulfonic acid, 2-methylidenepropane-1,3-disulfonic acid, 2-sulfoethyl methacrylate, sulfopropyl methacrylate, sulfopropyl acrylate, allyl phosphonic acid, styrene sulfonic acid, 2-acrylamido-2-methylpropane disulfonic acid, etc.; and salts of these monomers, such as alkali metal salts, alkaline earth metal salts or ammonium salts. In this list, the mentioned strong acid monomers with sulfonic acid functional groups do not include the hydrated crystalline forms of 2-acrylamido-2-methylpropanesulfonic acid according to the invention.

[0130] According to a particular embodiment, the copolymer is advantageously obtained from 1 to 99 mol %, preferably from 2 to 60 mol %, and more preferably from 3 to 25 mol % of anionic monomers relative to the total number of monomers, these percentages including monomers of hydrated crystalline form of 2-acrylamido-2-methylpropanesulfonic acid according to the invention.

[0131] The cationic monomers that may be used in the present invention may be selected in particular from acrylamide, acrylic, vinyl, allyl, or maleic type monomers with phosphonium or quaternary ammonium functional groups. In particular, but without limitation, mention may be made of quaternary dimethylaminoethyl acrylate (ADAME), quaternary dimethylaminoethyl methacrylate (MADAME), dimethyldiallylammonium chloride (DADMAC), acrylamidopropyltrimethylammonium chloride (APTAC), and methacrylamidepropyltrimethylammonium chloride (MAPTAC). The quaternizing agent may be selected from alkyl chlorides, dialkyl sulfates, or alkyl halides. Preferably, the quaternizing agent is selected from methyl chloride or diethyl sulfate.

[0132] The zwitterionic monomer may be an acrylamide type, an acrylic type, a vinyl type, an allylic type, or a maleic acid type having an amine or quaternary ammonium functional group and an acid functional group such as a carboxylic acid, a sulfonic acid, or a phosphoric acid. Specifically, but not limited to, dimethylaminoethyl acrylates such as 2-((2-(acryloyloxy)ethyl)dimethylammonio)ethane-1-sulfonate, 3-((2-(acryloyloxy)ethyl)dimethylammonio)propane-1-sulfonate, 4-((2-(acryloyloxy)ethyl)dimethylammonio)butane-1-sulfonate, and [2-(acryloyloxy)ethyl](dimethylammonio)acetate. methacrylate derivatives, dimethylaminoethyl methacrylates such as 2-((2-(methacryloyloxy)ethyl)dimethylammonio)ethane-1-sulfonate, 3-((2-(methacryloyloxy)ethyl)dimethylammonio)propane-1-sulfonate, 4-((2-(methacryloyloxy)ethyl)dimethylammonio)butane-1-sulfonate, and [2-(methacryloyloxy)ethyl](dimethylammonio)acetate; dimethylaminopropyl acrylamide derivatives such as 2-((3-acrylamidopropyl)dimethylammonio)ethane-1-sulfonate, 3-((3-acrylamidopropyl)dimethylammonio)propane-1-sulfonate, 4-((3-acrylamidopropyl)dimethylammonio)butane-1-sulfonate, [3-(acryloyloxy)propyl](dimethylammonio)acetate, dimethylaminopropyl methyl acrylamide derivatives such as 2-((3-methacrylamidopropyl)dimethylammonio)ethane-1-sulfonate, 3-((3-methacrylamidopropyl)dimethylammonio)propane-1-sulfonate, 4-((3-methacrylamidopropyl)dimethylammonio)butane-1-sulfonate, and [3-(methacryloyloxy)propyl](dimethylammonio)acetate may be mentioned.

[0133] Monomers that are hydrophobic in nature may also be used in the present invention. They are preferably selected from the group consisting of (meth)acrylic acid esters with alkyl, arylalkyl, propoxylated, ethoxylated, or ethoxylated and propoxylated chains; (meth)acrylamide derivatives with alkyl, arylalkyl, propoxylated, ethoxylated, ethoxylated and propoxylated chains, or dialkyl chains; alkylarylsulfonates.

[0134] When a monomer having hydrophobic properties is used, its amount advantageously ranges from 0.001 to 3 mol % relative to the total amount of monomers.

[0135] Monomers with fluorescent functional groups may also be used within the scope of the present invention. Monomers with fluorescent functional groups may be detected by any suitable method, for example fluorimetry with a fixed wavelength fluorimeter. Generally, monomers with fluorescent functional groups are detected at excitation and emission maxima that can be determined using a scanning fluorimeter.

[0136] These monomers having fluorescent functional groups are selected, for example, from monomers including sodium styrene sulfonate and styrene sulfonate.

[0137] According to the invention, the (co)polymers used may have linear, branched, crosslinked, star or comb structures, which can be obtained by the choice of initiators, chain transfer agents, polymerization techniques such as RAFT (reversible addition-fragmentation chain transfer), NMP (nitroxide mediated polymerization) or controlled radical polymerization known as ATRP (atom transfer radical polymerization), the incorporation or concentration of structural monomers, etc.

[0138] Generally, the (co)polymers do not require the development of any particular polymerization method. In fact, they can be obtained according to polymerization techniques known to those skilled in the art. It may be, in particular, solution polymerization, gel polymerization, precipitation polymerization, emulsion polymerization (aqueous or reverse phase), suspension polymerization, reactive extrusion polymerization or micellar polymerization.

[0139] According to a particular embodiment of the invention, the (co)polymer may be post-hydrolyzed. Post-hydrolysis is the reaction of the (co)polymer after polymerization. This step consists of reacting hydrolyzable functional groups on the non-ionic monomers, such as amide or ester functional groups, with a base. During this post-hydrolysis step of the (co)polymer, the number of carboxylic acid functional groups is increased. The reaction of the base with the amide or ester functional groups generates carboxylate groups in the (co)polymer product.

[0140] The (co)polymer may be in the form of a liquid, gel or solid if its preparation includes a drying step such as spray drying, tumble drying, drying by electromagnetic radiation (microwave, radio frequency) or fluidized bed drying.

[0141] According to the invention, the (co)polymer may be linear, structured or crosslinked. By structured (co)polymer is meant a non-linear (co)polymer with side chains to obtain a highly entangled state which results in a very high viscosity at low gradient when the (co)polymer is dissolved in water.

[0142] Additionally, the (co)polymer may comprise: at least one structuring agent that may be selected from the group comprising unsaturated polyethylenic monomers (having at least two unsaturated functional groups), such as vinyl, allyl, acrylic and epoxy functional groups, of which mention may be made, for example, of methylene-bis-acrylamide (MBA), triallylamine, tetraallylammonium chloride, 1,2-dihydroxyethylenebis-(N-acrylamide), and / or - by macroinitiators such as polyperoxides, polyazoics, and multifunctional chain transfer agents such as polymercaptan (co)polymers and polyols; and / or by functionalized polysaccharides, It may be structured or crosslinked.

[0143] The amount of branching / crosslinking agent in the monomer mixture is advantageously less than 4% by weight, more advantageously less than 1% by weight and even more advantageously less than 0.5% by weight relative to the monomer content. According to a particular embodiment, it may be at least equal to 0.00001% by weight relative to the monomer content.

[0144] According to a particular embodiment, the (co)polymer may comprise at least one LCST group.

[0145] According to the general knowledge of the skilled artisan, an LCST group corresponds to a group whose water solubility at a given concentration is modified above a certain temperature and as a function of the salt concentration. It is a group that has a heat transition temperature that defines its lack of affinity with the solvent. The lack of affinity with the solvent leads to opalescence or loss of transparency, which can be due to precipitation, aggregation, gelation, or an increase in the viscosity of the medium. The lowest transition temperature is known as the "LCST" (Lower Critical Solution Temperature). At each concentration of LCST groups, a heat transition temperature is observed. It is higher than the LCST, which is the lowest point of the curve. Below this temperature, the (co)polymer is soluble in water, and above this temperature, the (co)polymer loses its solubility in water.

[0146] According to a particular embodiment, the (co)polymer may comprise at least one UCST group.

[0147] According to the general knowledge of the skilled artisan, the UCST group corresponds to a group whose water solubility at a given concentration is modified above a certain temperature and as a function of the salt concentration. It is a group that has a cooling transition temperature that defines its lack of affinity with the solvent. The lack of affinity with the solvent leads to opalescence or loss of transparency, which can be due to precipitation, aggregation, gelation, or an increase in the viscosity of the medium. The highest transition temperature is known as the "UCST" (upper critical solution temperature). At each concentration of the UCST group, a cooling transition temperature is observed. It is lower than the UCST, which is the highest point of the curve. Above this temperature, the (co)polymer is soluble in water, below this temperature, the (co)polymer loses its water solubility.

[0148] According to the invention, the (co)polymers advantageously have a high molecular weight. By "high molecular weight" is meant a molecular weight of at least 1 million g / mol, preferably between 2 and 40 million g / mol, more preferably between 5 and 30 million g / mol. Molecular weight is understood as weight average molecular weight.

[0149] According to one embodiment of the invention, the copolymer may be obtained by (co)polymerization of at least one water-soluble monomer with at least one monomer of a hydrated crystalline form of 2-acrylamido-2-methylpropanesulfonic acid and / or one of its salts.

[0150] In the broadest sense, unless otherwise specified, "2-acrylamido-2-methylpropanesulfonic acid in hydrated crystalline form" means the acid form and / or the salified form. The same applies to the anionic monomers mentioned in the present description, which may mean the acid form and / or the salified form, as for example in the case of acrylic acid.

[0151] The salt forms are advantageously obtained from compounds chosen from among alkali metal or alkaline earth metal hydroxides, alkali metal or alkaline earth metal oxides, ammonia, amines having the following formula NR1R2R3, where R1, R2 and R3 are advantageously hydrocarbon radicals, in particular alkyl radicals, or alkali metal or alkaline earth metal carbonates. The preferred alkali metal is sodium.

[0152] The acid form of the monomers may be salified before and / or during and / or after the (co)polymerization of the monomers.

[0153] The (co)polymers of the present invention are preferably water-soluble.

[0154] Advantageously, the (co)polymer has a molecular weight, based on mass, of 5000 to 40,000,000 g / mol, preferably of 1,250,000 to 35,000,000 and even more preferably of 2,750,000 to 30,000,000 g / mol.

[0155] The molecular weight is determined by the intrinsic viscosity of the (co)polymer. The intrinsic viscosity may be measured by methods known to those skilled in the art and may be calculated from the low viscosity values ​​at different (co)polymer concentrations by a graphical method consisting of recording the low viscosity values ​​(y-axis) against the concentration (x-axis) and extrapolating the curve to zero concentration. The intrinsic viscosity values ​​are recorded on the y-axis or are recorded using the least squares method. The molecular weight can then be determined by the Mark-Houwink formula: [η] = KM α [η] represents the intrinsic viscosity of the (co)polymer as determined by a method for measuring the viscosity of the solution. K represents an empirical constant. M represents the molecular weight of the (co)polymer. α represents the Mark-Houwink coefficient. K and α depend on the particular (co)polymer-solvent system.

[0156] Another feature of the present invention relates to the use of (co)polymers made from hydrated crystalline forms of at least one of 2-acrylamido-2-methylpropanesulfonic acid or its salts. In these (co)polymers, 2-acrylamido-2-methylpropanesulfonic acid may be partially neutralized before, during, or after the (co)polymerization of 2-acrylamido-2-methylpropanesulfonic acid. More particularly, the present invention relates to the use of these (co)polymers in the oil and gas, hydraulic fracturing, paper, water treatment, construction, mining, cosmetics, textiles, or detergents industries. Preferably, the (co)polymers are used in the field of enhanced oil and gas recovery.

[0157] The invention and the advantages obtained therefrom will become clearer on reading the following figures and examples, given to illustrate the invention without in any way limiting it. EXAMPLES

[0158] Example 1 Synthesis of 2-acrylamido-2-methylpropanesulfonic acid To a 2000 mL jacketed reactor equipped with a stirrer was added 1522 grams of acrylonitrile containing 0.4% by weight water and 180 grams of oleum titrated to 104% H2SO4 (18% oleum). The mixture was stirred for 1 hour and cooled via the reactor jacket to maintain the temperature of the sulfonation mixture at -20°C.

[0159] To the above sulfonation mixture was added 97 grams of isobutylene at a flow rate of 1.6 grams / minute.

[0160] The temperature of the mixture was controlled at 45° C. during the addition of isobutylene. Particles of 2-acrylamido-2-methylpropanesulfonic acid precipitated in the mixture, and the solid content was about 20% by weight. The reaction mixture was filtered through a Buchner funnel and dried under vacuum at 50° C. The resulting solid was 2-acrylamido-2-methylpropanesulfonic acid, and was present in the form of a very fine white powder.

[0161] Observation using an optical microscope (FIG. 10) and a scanning electron microscope (FIG. 12) revealed that the crystals were needle-shaped.

[0162] Example 2 Formation of hydrated crystalline forms of 2-acrylamido-2-methylpropanesulfonic acid To a 2000 mL jacketed reactor was added 500 grams of 2-acrylamido-2-methylpropanesulfonic acid obtained in Example 1 and 460 grams of sulfuric acid with a concentration of 10% H2SO4.

[0163] To the above mixture was added 250 mg of 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxyl.

[0164] The mixture was stirred at 20° C. for 10 minutes to form Suspension A.

[0165] Suspension A was heated to a temperature of 60° C. and maintained at this temperature for 20 minutes to form solution B.

[0166] Solution B was cooled to a temperature of 10° C. The cooling time from 60° C. to 10° C. was 6 hours. A suspension C of 2-acrylamido-2-methylpropanesulfonic acid crystals was obtained. The suspension C was filtered in a vertical Robatel centrifugal dryer. A solid of composition 1 containing 80% by mass of 2-acrylamido-2-methylpropanesulfonic acid crystals was obtained.

[0167] Observation using an optical microscope (FIG. 11) and a scanning electron microscope (FIG. 13) revealed that the crystals were cubic.

[0168] Example 3 NMR Analysis of Products from Examples 1 and 2 The 2-acrylamido-2-methylpropanesulfonic acid solid obtained in Example 1 and its hydrated crystalline form obtained in Example 2 were analyzed by proton nuclear magnetic resonance (NMR) spectroscopy.

[0169] The samples were dissolved in D2O. The Bruker NMR instrument had a frequency of 400 MHz and was fitted with 5 mm BBO BB- 1 It was equipped with an H probe.

[0170] The two proton spectra (Figure 1) were identical and the peak assignments were consistent with the molecular structure of 2-acrylamido-2-methylpropanesulfonic acid.

[0171] Example 4 X-ray diffraction analysis The solids obtained in Examples 1 and 2 were pre-ground to form powders and analyzed by X-ray diffraction over an angular range of 10 to 90°. The instrument used was a Rigaku miniflex II diffractometer equipped with a copper source.

[0172] The inventors have found that the solid obtained from Example 2 (Figure 3) has a 2-theta X-ray diffraction pattern with the following characteristic peaks: 10.58°, 11.2°, 12.65°, 13.66°, 16.28°, 18.45°, 20°, 20.4°, 22.5°, 25.5°, 25.88°, 26.47°, 28.52°, 30.28°, 30.8°, 34.09°, 38.19°, 40.69°, 41.82°, 43.74°, 46.04° 2Theta Degrees (+ / - 0.1°)

[0173] Example 5 Fourier transform infrared measurement The Fourier transform infrared measuring device has an accuracy of 8 cm. -1 The model was the Perkin Elmer Spectrum 100.

[0174] The solids obtained in Examples 1 and 2 were sieved through a 100 μm sieve. The particles remaining on the sieve were dried and placed in an oven at 60° C. for at least 4 hours.

[0175] 10 mg of the solid was accurately weighed and mixed with 500 mg of potassium bromide (KBr). The mixture was then compressed in a hydraulic press under a pressure of at least 10 bar.

[0176] The inventors have determined that the following frequency bands (FIG. 5) are characteristic of the hydrated crystalline form of 2-acrylamido-2-methylpropanesulfonic acid: 3280cm -1 , 3126cm -1 , 1657cm -1 , 1595cm -1 , 1453cm -1 , 1395cm -1 , 1307cm -1 , 1205cm -1 , 1164cm -1 , 1113cm -1 , 1041cm -1 , 968cm -1 , 885cm -1 , 815cm -1 , 794cm -1

[0177] The infrared spectrum of the solid according to Example 1 (Figure 4) did not show the same peaks.

[0178] Example 6 Differential Scanning Calorimetry (DSC) The instrument used was a DSC131 EVO by Setaram.

[0179] The solids obtained in Examples 1 and 2 were analyzed under a nitrogen flow with a heating gradient of 10°C / min. The initial temperature was 30°C and the product was heated to 220°C.

[0180] The thermogram of the crystals of Example 1 (FIG. 6) showed a heat effect at a temperature of 191.5° C., which is commonly regarded as the melting / decomposition point of 2-acrylamido-2-methylpropanesulfonic acid.

[0181] The thermogram of the crystals from Example 2 (FIG. 7) showed three additional thermal events visible at 70.8, 103.4, and 152.2° C. The peak at 187.4° C. is associated with the decomposition of the molecule of 2-acrylamido-2-methylpropanesulfonic acid.

[0182] In comparison, the thermogram of the crystals from Example 1 did not show a decomposition peak at 191.5° C. (FIG. 6).

[0183] Example 7 Acid-Base Titration To a 1000 mL beaker was added 500 mL of demineralized water and 100 g from Example 1. A magnetic stir bar was added to allow mixing of the solution.

[0184] A graduated burette was filled with 30% sodium hydroxide.

[0185] A pH meter was added to allow monitoring of the pH during the addition of the sodium hydroxide.

[0186] The initial pH of the aqueous solution was less than 1. Sodium hydroxide was added until a pH of 7 was obtained.

[0187] 64 g of 30% sodium hydroxide was added.

[0188] The molar mass of 2-acrylamido-2-methylpropanesulfonic acid was 207 g / mol. Equivalence point calculation showed that the solid obtained in Example 1 contained 99% by weight of 2-acrylamido-2-methylpropanesulfonic acid (titration of acid functional groups).

[0189] The solid obtained in Example 2 was titrated using the same protocol. 59 g of sodium hydroxide was added to 100 g of the solid obtained in Example 2. The equivalence point calculation showed that the solid obtained in Example 2 contained 92% by weight of 2-acrylamido-2-methylpropanesulfonic acid.

[0190] The remaining 8% was water. This 2-acrylamido-2-methylpropanesulfonic acid / H2O mass ratio (92 / 8) corresponds to a 1:1 molar ratio.

[0191] The solid obtained in Example 2 was therefore a hydrated crystalline form of 2-acrylamido-2-methylpropanesulfonic acid.

[0192] Example 8 Measurement of Minimum Ignition Energy (MIE) The minimum ignition energy was determined according to standard NF EN 13821.

[0193] The flammable gas detector was a vertical Hartmann tube. The dust dispersion system was a mushroom system.

[0194] The total inductance was less than 25 microhenries. The discharge voltage was 5 kV to 15 kV. The electrodes were made of brass and were spaced at least 6 mm apart.

[0195] Different energies and dispersed masses were tested and are summarized in the table below.

[0196] It is clear that the hydrated crystalline form poses a much lower explosion risk than the needle-like form obtained in Example 1.

[0197] [Table 1]

[0198] [Table 2]

[0199] Example 9 Particle size measurement The solids obtained in Examples 1 and 2 were analyzed by laser diffraction to determine their particle size distribution.

[0200] The instrument used was a Cilas 1190.

[0201] In the case of the crystal of Example 1, d 50The values ​​were around 40 μm, with 90% of the particles being smaller than 200 μm (FIG. 8).

[0202] In the case of the crystal of Example 2, d 50 The value was about 600 μm, with 90% of the particles being smaller than 1500 μm (FIG. 9). The crystals contained less than 10% of the particles smaller than 300 μm.

[0203] Example 10 Measurement of specific surface area The solids obtained in Examples 1 and 2 were degassed at room temperature for 24 hours.

[0204] The device for measuring the specific surface area by adsorption measurements was a TriStar II Micromeritics device connected to a Micromeritics Smart VacPrep. The measurement temperature was -196°C.

[0205] [Table 3]

[0206] Example 11 Preparation protocol for the hydrated crystalline form of the sodium salt of 2-acrylamido-2-methylpropanesulfonic acid To a jacketed 2000 mL reactor equipped with a condenser, pH meter, and stirrer was added 500 grams of the hydrated crystalline form of acrylamido-2-methylpropanesulfonic acid from Example 2 and 770 grams of water. The pH of this mixture was less than 1.

[0207] A 50% strength sodium hydroxide solution was prepared in the dropping funnel. This caustic solution was added to the reaction mixture over a period of 120 minutes. The temperature was controlled to be less than 30°C.

[0208] The pH remained below 5 during the addition of sodium hydroxide.

[0209] 175 grams of a 50% by weight concentration sodium hydroxide solution were added.

[0210] The resulting mixture was a solution of 2-acrylamido-2-methylpropanesulfonic acid sodium salt with a concentration of 35% by mass.

[0211] Example 12 Preparation of acrylamide / 2-acrylamido-2-methylpropanesulfonic acid (75 / 25 mol%) copolymer P1 in hydrated crystalline form 549.5 g of deionized water, 520.5 g of a 50% solution of acrylamide, 97.6 g of a 50% solution of sodium hydroxide, 16.2 g of urea, and 316.2 g of 2-acrylamido-2-methylpropanesulfonic acid crystals obtained in Example 2 are added to a 2000 ml beaker.

[0212] The solution thus obtained is cooled to 0-5°C and transferred to an adiabatic polymerization reactor and nitrogen bubbling is carried out for 30 minutes to remove any traces of dissolved oxygen.

[0213] Next, in the reactor: 0.75 g of 2,2'-azobisisobutyronitrile, - 1.5 ml of a solution containing 5 g / l of 2,2'-azobis[2-(2-imidazolin-2-yl)propane dihydrochloride], 1.5 ml of a solution containing 3 g / l sodium hypophosphite, 2.25 ml of a solution containing 1 g / l tert-butyl hydroperoxide, - 2.25 ml of a 1 g / l solution of ammonium iron(II) sulfate hexahydrate (Mohr's salt), Add the following.

[0214] After a few minutes, the nitrogen inlet is closed and the reactor is sealed. The polymerization reaction is carried out for 1-5 hours until a peak temperature is reached. The resulting rubbery gel is chopped into particles with a diameter of 1-6 mm.

[0215] The gel is then dried and ground to obtain the polymer in powder form.

[0216] (Example 13) Preparation of acrylamide / hydrated non-crystalline 2-acrylamido-2-methylpropanesulfonic acid (75 / 25 mol%) copolymer P'1 The copolymer is prepared as in Example 12, replacing the crystalline 2-acrylamido-2-methylpropanesulfonic acid hydrate (Example 2) with the hydrated 2-acrylamido-2-methylpropanesulfonic acid obtained in Example 1, which is not in crystalline form.

[0217] Example 14 Determination of the resistance to chemical degradation of solutions of copolymers P1 and P'1 of equal molecular weight Tests of the resistance to chemical degradation of polymers P1 and P'1 with a molecular weight of 9 million were carried out under aerobic conditions in a brine composed of water, 37000 ppm NaCl, 5000 ppm Na2SO4, and 200 ppm NaHCO3, in the presence of different concentrations of iron(II) (2, 5, 10, and 20 ppm). These tests were carried out on a polymer (P'1) prepared from 2-acrylamido-2-methylpropanesulfonic acid or at least one of its salts in amorphous form, and on a polymer (P1) prepared from 2-acrylamido-2-methylpropanesulfonic acid or at least one of its salts in crystalline form. Both polymers have the same chemical composition. The results obtained after 24 hours of contacting the polymer solution with the contaminant are shown in Figure 14.

[0218] The inventors' observations show that at each concentration of iron(II), the viscosity reduction of polymer P1 is smaller than that of the comparable polymer P'1.

[0219] Example 15 Determination of thermal degradation resistance of solutions of polymers of equal molecular weight. Tests of thermal degradation resistance of polymers P1 and P'1 with a molecular weight of 9 million were carried out under anaerobic conditions at an active concentration of 2000 ppm in a brine composed of water, 30000 ppm NaCl, and 3000 ppm CaCl2.2H2O. These tests were carried out on a polymer (P'1) made from 2-acrylamido-2-methylpropanesulfonic acid or at least one of its salts in amorphous form, and on a polymer (P1) made from 2-acrylamido-2-methylpropanesulfonic acid or at least one of its salts in crystalline form. Both polymers have the same chemical composition. The polymer solutions were aged at 90°C for 6 months. The obtained results in terms of viscosity reduction are shown in Figure 15. Our observations show that the viscosity reduction of polymer P1 is smaller than that of the comparable polymer P'1.

[0220] Example 16 Preparation of homopolymer P2 from the hydrated crystalline form of 2-acrylamido-2-methylpropanesulfonic acid 390.5 g of deionized water, 262 g of 50% sodium hydroxide solution, and 847.5 g of 2-acrylamido-2-methylpropanesulfonic acid crystals from Example 2 are added to a 2000 ml beaker.

[0221] The solution thus obtained is cooled to 5-10° C. and transferred to an adiabatic polymerization reactor and nitrogen bubbling is carried out for 30 minutes to remove any traces of dissolved oxygen.

[0222] Next, in the reactor: 0.45 g of 2,2'-azobisisobutyronitrile, - 1.5 ml of a solution containing 2.5 g / l of 2,2'-azobis[2-(2-imidazolin-2-yl)propane dihydrochloride], 1.5 ml of a 1 g / l solution of sodium hypophosphite, 1.5 ml of a solution containing 1 g / l tert-butyl hydroperoxide, - 1.5 ml of a 1 g / l solution of ammonium iron(II) sulfate hexahydrate (Mohr's salt), Add the following.

[0223] After a few minutes, the nitrogen inlet is closed and the reactor is sealed. The polymerization reaction is carried out for 2-5 hours until the peak temperature is reached. The resulting rubbery gel is chopped into small pieces and dried to obtain a coarse powder, which is itself crushed and sieved to obtain the polymer in powder form.

[0224] (Example 17) Preparation of homopolymer P'2 from hydrated, non-crystalline 2-acrylamido-2-methylpropanesulfonic acid The polymer is prepared as in Example 16, replacing the hydrated crystalline form of 2-acrylamido-2-methylpropanesulfonic acid with the non-hydrated crystalline form of 2-acrylamido-2-methylpropanesulfonic acid synthesized in Example 1.

[0225] (Example 18) Determination of the resistance to chemical degradation of solutions of polymers P2 and P'2 Tests of the resistance to chemical degradation of polymers P2 and P'2 with a molecular weight of 5.3 million Da were carried out under aerobic conditions in a brine solution composed of water, 37,000 ppm NaCl, 5,000 ppm Na2SO4, and 200 ppm NaHCO3, in the presence of various concentrations of iron(II) (2, 5, 10, and 20 ppm). These tests were carried out on a polymer (P'2) prepared from 2-acrylamido-2-methylpropanesulfonic acid or at least one of its salts in amorphous form, and on a polymer (P2) prepared from 2-acrylamido-2-methylpropanesulfonic acid or at least one of its salts in crystalline form. Both polymers have the same chemical composition. The results obtained after 24 hours of contact of the polymer solution with the contaminant are shown in Figure 16.

[0226] The inventors' observations show that at each concentration of iron(II), the viscosity reduction of polymer P2 is smaller than that of the comparable polymer P'2.

[0227] (Example 19) Preparation of post-hydrated copolymer P3 of acrylamide / hydrated crystalline form of 2-acrylamido-2-methylpropanesulfonic acid (75 / 25 mol%) 761.9 g of deionized water, 574.2 g of a 50% solution of acrylamide, 35.9 g of a 50% solution of sodium hydroxide, 11.7 g of urea, and 116.3 g of 2-acrylamido-2-methylpropanesulfonic acid crystals obtained in Example 2 are added to a 2000 ml beaker.

[0228] The solution thus obtained is cooled to 0-5°C and transferred to an adiabatic polymerization reactor and nitrogen bubbling is carried out for 30 minutes to remove any traces of dissolved oxygen.

[0229] Next, in the reactor: 0.45 g of 2,2'-azobisisobutyronitrile, 1.5 ml of a solution containing 5 g / l of 2,2'-azobis[2-(2-imidazolin-2-yl)propane dihydrochloride], 1.5 ml of a 1 g / l solution of sodium hypophosphite, 2.25 ml of a solution containing 1 g / l tert-butyl hydroperoxide, - 3.0 ml of a 1 g / l solution of ammonium iron(II) sulfate hexahydrate (Mohr's salt), Add the following.

[0230] After a few minutes, the nitrogen inlet is closed and the reactor is sealed. The polymerization reaction is carried out for 2-5 hours until a peak temperature is reached. The resulting rubbery gel is chopped into particles with a diameter of 1-6 mm.

[0231] 500.0 g of the above ground gel is then mixed with 18.0 g of 50% sodium hydroxide solution and the mixture is heated and maintained at a temperature of 90° C. for 90 minutes.

[0232] The gel is then dried and ground to obtain the polymer in powder form.

[0233] (Example 20) Preparation of post-hydrated copolymer P'3 of acrylamide / hydrated non-crystalline 2-acrylamido-2-methylpropanesulfonic acid (75 / 25 mol%) The copolymer is prepared as in Example 19, replacing the hydrated crystalline form of 2-acrylamido-2-methylpropanesulfonic acid (Example 2) with the non-hydrated crystalline form of 2-acrylamido-2-methylpropanesulfonic acid synthesized in Example 1.

Claims

1. (Co)polymers of 2-acrylamido-2-methylpropanesulfonic acid, at least in acid form and / or salt form, at least a portion of the 2-acrylamido-2-methylpropanesulfonic acid is in a hydrated crystalline form and has an X-ray powder diffraction pattern including peaks at 10.58°, 11.2°, 12.65°, 13.66°, 16.28°, 18.45°, 20°, 20.4°, 22.5°, 25.5°, 25.88°, 26.47°, 28.52°, 30.28°, 30.8°, 34.09°, 38.19°, 40.69°, 41.82°, 43.74°, and 46.04° degrees two-theta (+ / - 0.1°); A (co)polymer of 2-acrylamido-2-methylpropanesulfonic acid in a hydrated crystalline form, the molar ratio of water / 2-acrylamido-2-methylpropanesulfonic acid being 1.

2. The hydrated crystalline form, 2-acrylamido-2-methylpropanesulfonic acid, reacts at 3280 cm -1 , 3126cm -1 , 1657cm -1 , 1595cm -1 , 1453cm -1 , 1395cm -1 , 1307cm -1 , 1205cm -1 , 1164cm -1 , 1113cm -1 , 1041cm -1 , 968cm -1 , 885cm -1 , 815cm -1 , and 794 cm -1 (+ / -8cm -1 2. The (co)polymer according to claim 1, characterized in that it exhibits a Fourier transform infrared spectrum containing a peak of

3. 3. The (co)polymer according to claim 1 or 2, characterized in that 2-acrylamido-2-methylpropanesulfonic acid in its hydrated crystalline form exhibits a minimum ignition energy of more than 400 mJ.

4. 4. The (co)polymer according to claim 1, characterized in that the hydrated crystalline form of 2-acrylamido-2-methylpropanesulfonic acid exhibits four thermal phenomena at 70°C, 100°C, 150°C and 190°C (+ / - 10°C) using differential scanning calorimetry.

5. said (co)polymer further comprising at least one monomer selected from the group consisting of non-ionic monomers, cationic monomers, zwitterionic monomers, anionic monomers different from 2-acrylamido-2-methylpropanesulfonic acid in its hydrated crystalline form, monomers having hydrophobic properties, and mixtures thereof, the non-ionic monomer is selected from the group consisting of acrylamide, N-isopropylacrylamide, N,N-dimethylacrylamide, N-vinylformamide, acryloylmorpholine, N,N-diethylacrylamide, N-tert-butylacrylamide, N-tert-octylacrylamide, N-vinylpyrrolidone, N-vinylcaprolactam, N-vinyl-imidazole, hydroxyethyl methacrylamide, hydroxypropyl acrylate, isoprenol, and diacetone acrylamide; the cationic monomer is selected from the group consisting of quaternary dimethylaminoethyl acrylate (ADAME), quaternary dimethylaminoethyl methacrylate (MADAME), dimethyldiallylammonium chloride (DADMAC), acrylamidopropyltrimethylammonium chloride (APTAC), and methacrylamidopropyltrimethylammonium chloride (MAPTAC); The zwitterionic monomer is 2-((2-(acryloyloxy)ethyl)dimethylammonio)ethane-1-sulfonate, 3-((2-(acryloyloxy)ethyl)dimethylammonio)propane-1-sulfonate, 4-((2-(acryloyloxy)ethyl)dimethylammonio)butane-1-sulfonate, [2-(acryloyloxy)ethyl](dimethylammonio)acetate; 2-((2-(methacryloyloxy)ethyl)dimethylammonio)ethane-1-sulfonate, 3-((2-(methacryloyloxy)ethyl)dimethylammonio)propane-1-sulfonate, 4-((2-(methacryloyloxy)ethyl)dimethylammonio)butane-1-sulfonate, [2-(methacryloyloxy)ethyl](dimethylammonio) acetate; 2-((3-acrylamidopropyl)dimethylammonio)ethane-1-sulfonate, 3-((3-acrylamidopropyl)dimethylammonio)propane-1-sulfonate, 4-((3-acrylamidopropyl)dimethylammonio)butane-1-sulfonate, [3-(acryloyloxy)propyl](dimethylammonio)acetate; 2-((3-methacrylamidopropyl)dimethylammonio)ethane-1-sulfonate, 3-((3-methacrylamidopropyl)dimethylammonio)propane-1-sulfonate, 4-((3-methacrylamidopropyl)dimethylammonio)butane-1-sulfonate, and [3-(methacryloyloxy)propyl](dimethylammonio)acetate; the anionic monomer is selected from the group consisting of acrylic acid, methacrylic acid, itaconic acid, crotonic acid, maleic acid, fumaric acid, acrylamidoundecanoic acid, acrylamido-3-methylbutanoic acid, maleic anhydride, vinylsulfonic acid, vinylphosphonic acid, allylsulfonic acid, methallylsulfonic acid, 2-methylidenepropane-1,3-disulfonic acid, 2-sulfoethyl methacrylate, sulfopropyl methacrylate, sulfopropyl acrylate, allylphosphonic acid, styrenesulfonic acid, 2-acrylamido-2-methylpropanedisulfonic acid, 2-acrylamido-2-methylpropanesulfonic acid different from the hydrated crystalline form defined in claim 1, and salts of these monomers, 4. The method of claim 1, wherein the monomer having hydrophobic properties is selected from the group consisting of (meth)acrylic acid esters having alkyl, aryl alkyl, propoxylated, ethoxylated or ethoxylated and propoxylated chains; (meth)acrylamide derivatives having alkyl, aryl alkyl, propoxylated, ethoxylated, ethoxylated and propoxylated chains or dialkyl chains.

5. A (co)polymer according to any one of claims 1 to 4.

6. The salt form of 2-acrylamido-2-methylpropanesulfonic acid, which is in the hydrated crystalline form, can be prepared by reacting with an alkali metal or alkaline earth metal hydroxide, an alkali metal or alkaline earth metal oxide, ammonia, or a compound of the formula NR 1 R 2 R 3 (wherein R 1 , R 2 , and R 3 is a hydrogen atom or a carbon chain having 1 to 22 carbon atoms, with the proviso that R 1 , R 2 , and R 3 (Co)polymer according to any one of claims 1 to 5, characterized in that it is a salt of a compound selected from the group consisting of a carbonate of an alkali metal or an alkaline earth metal, wherein x is not at the same time a hydrogen atom.

7. 7. (Co)polymer according to any one of claims 1 to 6, characterized in that it is water-soluble or water-swellable or superabsorbent.

8. 8. (Co)polymer according to claim 1, characterized in that it has a weight average molecular weight of 2 to 40 million g / mol.

9. 9. (Co)polymer according to any one of claims 1 to 8, characterized in that it is linear, branched or crosslinked.

10. 10. (Co)polymer according to any one of claims 1 to 9, characterized in that it comprises from 1 to 100 mol % of 2-acrylamido-2-methylpropanesulfonic acid.

11. 11. Use of the (co)polymer according to any one of claims 1 to 10 in the oil and gas, hydraulic fracturing, paper, water treatment, construction or mining industries.

12. 11. Use of the (co)polymer according to any one of claims 1 to 10 in the cosmetics, textile or detergent industry.

Citation Information

Patent Citations

  • Synthesis process for 2-acrylamido-2-methyl propane sulfonic acid through continuous method

    CN102351744A

  • Refining method of 2-acrylamidyl-2-methul propanesulfonic acid coarse product and product thereof

    CN103664708A

  • Purification of 22acrylamidee22methylpropane sulfonic acid

    JP1979106427A

  • Production of highhpurity 22acrylamidee22 methylpropanesulfonic acid

    JP1979163524A

  • Production of high-purity 2-acrylamido-2-methylpropanesulfonic acid

    JP1993125037A